The Role of the Writing Centre in Enhancing Student Employability a Case Study of a University in South Africa - Ntando, Yamkela; Ndamase, Maxhobandile; Matenda, Stenford (Research in Social Sciences and Technology- OpenED Network, 2024)
In the quest of bridging the high graduate unemployment gap of South African graduates, universities introduced initiatives which sought to assist graduates gain the necessary working experience. South African graduates struggle to find sufficient employment due to lack of work experience. The peer-to-peer coaching led by senior students, who are postgraduate students, leads to the enhancement of graduate employability. Therefore, this paper sought to investigate the contribution of the writing centre in increasing the chances of employment for its consultants. In light of this, literature was consulted to reveal the role of the writing centre in promoting student employment. Unstructured interviews were conducted on fifteen (15) participants, who were identified through convenient sampling technique. Thematic analysis was adopted to analyse the collected data. The paper found that the programme equips students to be familiar with the working environment. The study further revealed that the writing centre office is under-capacitated financially. The study thus proposed that the programme must be financially supported by the university, Department of Higher Education and Training (DHET) and other external stakeholders to continue capacitating the development of students. The study, therefore, concluded that the writing centre office effectively promotes student employability and increases the working experience of writing centre consultants.